Local Government Autonomy In Nigeria: Struggles And Challenges - Doho, Ahmed Wali; Ahmed, Abdulkadir; Umar, Ado (Advances in Social Sciences Research Journal, 2018)
The history and development of local government system in Nigeria passed through two major administrative phases; the pre-colonial and colonial era which influenced de-concentration and the post-independence and 1976 era which was characterized by devolution of authority. Reforms were introduced but were characterized with some challenges. The study, therefore examined the trends, patterns and development of local government system in Nigeria. The researchers primarily made used of secondary source of information. At the end it was discovered that the tier is faced with constitutional problems, and it was recommended for review of 1999 constitution.